Virulence potential of faecal Escherichia coli strains isolated from healthy cows and calves on farms in Perm Krai - V. S. Mihailovskaya; N. B. Remezovskaya; I. N. Zhdanova; M. Starčič Erjavec; M. V. Kuznetsova (Вавиловский журнал генетики и селекции)
Cattle are a reservoir of pathogenic and potentially pathogenic Escherichia coli (E. coli) strains, which can pose a threat to human and animal health. The aim of the study was to evaluate the occurrence of 22 virulence-associated genes (VAGs), as well as the prevalence of antimicrobial drug resistance and three different bla-genes among 49 E. coli strains isolated from healthy cattle. The presence of VAGs that are common among diarrheagenic E. coli (DEC) strains and/or extraintestinal pathogenic E. coli (ExPEC) strains was determined by amplifying specific gene sequences by PCR. The following VAGs associated with DEC were found: east1 in 24.5 % of the studied E. coli strains, estI in 10.2 %, ehxA in 8.2 %, stx2 in 6.1 %, eltA in 4.1 %, estII and stx1 in 2.0 % of the studied strains. The prevalence of ExPEC VAGs was: fimH – 91.8 %, afa/draBC – 61.2 %, iutA – 44.9 %, flu – 32.7 %, sfaDE and hlyF – 30.6 %, iroN – 22.4 %, ompT and papC – 20.4 %, kpsMTII and hlyA – 18.4 %, iss – 14.3 %, usp – 2.0 %, cnf1 and iha were not detected among the studied strains. Based on the found co-occurrence of VAGs “classical”, hetero-pathogenic and hybrid-pathogenic E. coli strains were found. E. coli strains isolated from cows had a higher diarrheagenic potential, whereas E. coli strains isolated from calves more frequently contained genes associated with the ExPEC pathotype. Among the studied E. coli strains, 77.6 % were resistant to ampicillin, 49.0 % to tetracycline, 20.4 % to chloramphenicol, 16.3 % to cefoperazone, 16.3 % to ceftriaxone, 16.3 % to aztreonam, 14.3 % to cefepime, 10.2 % to norfloxacin, 10.2 % to ciprofloxacin, 6.1 % to levofloxacin and 2.0 % to gentamicin. All strains were sensitive to meropenem and amikacin. 32.7 % of the studied E. coli strains were found to be multidrug resistant, as they were resistant to at least three groups of antibiotics. With PCR, the blaTEM, blaSHV, and blaCTX-M genes were detected in 100, 31.6, and 26.3 %, respectively, of strains resistant to at least one of the beta-lactam antibiotics. Thus, it was shown that the studied faecal E. coli of healthy cows and calves had a high hetero-pathogenic potential, therefore in the future molecular genetic characterization of these bacteria shall be an important part of the epizootic monitoring.